2020
DOI: 10.17759/psyedu.2020120207
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Psychological Reactions at the Start of the Pandemic of COVID-19

Abstract: The goal of the work is to study the dynamics of psychological changes unfolding during the COVID-19 pandemic. The paper presents an analysis of the responses to the survey on the Internet, received from 03.22.2020 to 04.04.2020, when the spread of COVID-19 begins in Russia. The study was conducted on the Internet using Google Forms. Links to the survey were posted on social networks. The survey involved 430 people, including 188 people in Moscow, and the answers were divided into 3 groups with respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(11 citation statements)
references
References 10 publications
0
10
0
1
Order By: Relevance
“…The SARS-CoV-2 virus is able to directly influence the activity of the central nervous system and cause psychiatric and neurological disorders affecting cognition and emotional regulation [9]. This affects the level of stress resistance in an emergency, and changes the repertoire of behavioral coping strategies used to overcome stress [10]. The choice of handling methods in the case of COVID-19 is still insufficiently covered in the modern scientific literature [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…The SARS-CoV-2 virus is able to directly influence the activity of the central nervous system and cause psychiatric and neurological disorders affecting cognition and emotional regulation [9]. This affects the level of stress resistance in an emergency, and changes the repertoire of behavioral coping strategies used to overcome stress [10]. The choice of handling methods in the case of COVID-19 is still insufficiently covered in the modern scientific literature [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…The current pandemic has a high-stress potential, as it threatens the life and health of the population (Kharlamenkova et al, 2020). Long-term preservation of the pandemic situation, its global scale, as well as the significance of changes in the daily life of every person, leads to a cumulative stress effect (Enikolopov et al, 2020). Measures of an epidemiological response (restriction of freedom), together with an infectious disease (method and rate of transmission of infection, the possibility of asymptomatic course), lead to an increase in anxiety, fear, depression (Arden & Chilcot, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The duration and uncertainty of the current situation, due to the special characteristics of the COVID-19, has evoked great fear in many people, jeopardizing the possibility of meeting basic human needs. An analysis of the occurred changes has shown that the situation associated with the coronavirus pandemic has a high stress potential, and the overall scale of the disaster allows us to consider it as a global traumatic stressor (Brunier & Harris, 2020;Enikolopov et al, 2020;Holmes et al, 2020). The cumulative stress effect caused by this situation is a factor of increasing anxiety, fear, melancholy and depression (due to the impossibility of a quick resolving the situation), the appearance or intensification of psychopathological symptoms, etc.…”
Section: Introductionmentioning
confidence: 99%
“…The cumulative stress effect caused by this situation is a factor of increasing anxiety, fear, melancholy and depression (due to the impossibility of a quick resolving the situation), the appearance or intensification of psychopathological symptoms, etc. (Enikolopov et al, 2020).…”
Section: Introductionmentioning
confidence: 99%